Assessment of lymph node metastasis of ≤20 mm non‐small cell lung cancer originating from superior segment compared to basal segment. Issue 3 (9th December 2022) - Yoshimura, Ryuichi; Deguchi, Hiroyuki; Tomoyasu, Makoto; Shigeeda, Wataru; Kaneko, Yuka; Iwai, Hidenobu; Saito, Hajime
Abstract: Background: Segmentectomy with curative intention is occasionally performed for early non‐small cell lung cancer (NSCLC). However, a major problem has been pointed out, in that the rate of locoregional recurrence is higher after segmentectomy than after lobectomy. This study aimed to investigate differences in rates of lymph node metastasis between segment 6 and basal segment NSCLC as potential candidates for segmentectomy and to explore factors associated with locoregional recurrence of segmentectomy. Methods: We retrospectively analyzed 461 patients with lower lobe NSCLC who underwent segmentectomy or lobectomy with mediastinal lymph node dissection between 2011 and 2021. Among these, 122 patients with clinical N0 NSCLC, diameter ≤ 20 mm, and consolidation tumor ratio >0.5 were analyzed. Results: The 122 patients were divided into a segment 6 group ( n  = 51) and a basal segment group ( n  = 71). Frequency of lymph node metastasis was significantly higher in the segment 6 group (17.7%) than in the basal segment group (4.2%; p  = 0.01). Metastases to lymph node station 7 were seen in five of 122 patients (4.1%). Hilar lymph node metastasis occurred in nine of 122 patients (7.4%). Notably, metastases to station 11, 11i and 11 s lymph nodes were the most frequent patterns for hilar lymph nodes (41.7%). Conclusions: Station 11 lymph nodes are adjacent to the remaining lung segment or pulmonary artery in S6 segmentectomy or basal segmentectomy. Part of the NSCLC in segment 6 patients may thus be considered for lobectomy owing to the difficulty of complete dissection of station 11 lymph nodes. Abstract : Complete hilar lymph node dissection or qualitative diagnosis be performed with curative segmentectomy. In particular, part of the NSCLC in segment 6 patients may be a candidate for lobectomy because of the difficulty of complete dissection of station 11 lymph node.